The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1177/1687814017692493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impeller trim on performance of two-stage self-priming centrifugal pump

Abstract: In order to save energy by broadening its application range, the influence of impeller trim on the performance of a twostage self-priming centrifugal pump was numerically studied. The hydraulic performance experiments and self-priming experiments were carried out. And the unsteady performance of pressure fluctuation and radial force in the pump was analyzed. The results show that with the increase in impeller trim quantity, the best efficiency point of the pump would move to the small flow rate condition. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…where ε is the dissipation rate of turbulent kinetic energy, which is already available in the turbulence model. To quantify the influence of entropy production, the power lost by entropy production in a certain domain can be estimated by integrating the dissipation rate in the whole domain, as illustrated by Equation (6).…”
Section: Hydraulic Loss Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where ε is the dissipation rate of turbulent kinetic energy, which is already available in the turbulence model. To quantify the influence of entropy production, the power lost by entropy production in a certain domain can be estimated by integrating the dissipation rate in the whole domain, as illustrated by Equation (6).…”
Section: Hydraulic Loss Estimation Methodsmentioning
confidence: 99%
“…Existing research indicates that the gap between the impeller and the volute tongue has a significant impact on the efficiency and radial force of centrifugal pumps [ 4 , 5 ]. Wang et al [ 6 ] reported that trimming impellers in a two-stage self-priming centrifugal pump decreased the radial force on the radial guide vanes and volute; however, the self-priming time increased. Both Yang [ 7 ] and Sanjay [ 8 ] experimentally investigated centrifugal pumps running in turbine mode and determined that impeller trimming could effectively influence efficiency, but the results varied.…”
Section: Introductionmentioning
confidence: 99%
“…Yi (1991) and Chen (1998;1990) undertook many experimental studies on the self-priming centrifugal pump, including on the design method, factors influencing the selfpriming performance, the effect of the reflux hole on self-priming performance curves, the correlations among reflux hole area, self-priming time and suction lift and the empirical equation for the reflux hole critical area. Wang (2017) studied the effects of impeller trim on performance of two-stage selfpriming centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%
“…Based on numerical simulation and test on impellers trimmed, Wang et al [9,10] analyzed the pressure pulsation characteristics and radial thrust behavior of a two-stage self-priming centrifugal pump after impeller trimming. Li et al [11] adopted volume of fluid (VOF) model to analyze air-liquid two-phase flow inside a self-priming pump numerically.…”
Section: Introductionmentioning
confidence: 99%